Smart Village Digital Strategy in Improving the Quality of Public Services in Rural Areas - Yusrianti, Yusrianti; Sapri, Sapri; Useng, Abd Razak (Department of Government Studies, Universitas Muhammadiyah Buton., 2025)
The quality of public services in rural areas still faces serious challenges, particularly regarding infrastructure limitations, low digital literacy, and suboptimal capacity of village officials. To address these issues, the Smart Village Program was implemented to digitize village administration to improve service efficiency, access to information, and community participation. This study aims to empirically test the effectiveness of the Smart Village Program in improving the quality of public services in Polewali Village, Sidenreng Rappang Regency. Using a quantitative approach and descriptive methods, the study involved 392 randomly selected respondents from the village population. Data was collected through observation, closed-ended questionnaires based on the Likert scale, and literature review, then analyzed using descriptive statistics, validity and reliability tests, and simple linear regression. The results indicate that the six pillars of the Smart Village Program have high effectiveness (average 80%), and public service quality has improved significantly (average 77.3%), particularly regarding reliability and assurance. These findings confirm that village digitalization can catalyze more adaptive and inclusive public service transformation. The Smart Village Program has the potential to become a model for sustainable local development, with policy implications for strengthening technological infrastructure, enhancing human resource capacity, and implementing active community engagement strategies.